A NEED TO CONTINUE THE TRADITION IN THE REGIONAL ARCHITECTURE OF THE PODHALE REGION - Palus, Kinga (European Scientific Journal, ESJ, 2014)
In Podhale, at the turn of the 20th and 21st centuries, the existing historical buildings are visibly endangered due to a lack of grounds for the mass development of trade and tourism. An increasing number of characteristic buildings keep disappearing from the landscape of Zakopane. Historical objects are often subject to destruction, are knocked down or thoughtlessly re-designed losing their original character. Every year preservation of the decreasing historical substance depends on various complex circumstances, different from the ones that assisted its construction, development and ’continuation’ in individual historical periods. The reason for preserving the traditional wooden architecture in the Podhale region results from a widely understood preservation of monuments nowadays, which is connected with cultural heritage and preservation of a place’s identity.